Sundanese "Kecap Anteuran" from the perspective of Japanese onomatopoeia - Risagarniwa, Yuyu Yohana; Lyra, Hera Meganova; Sopian, Rahmat (Wacana, Journal of the Humanities of Indonesia, 2025)
One of the distinctive features of the Sundanese language is the use of Kecap Anteuran (KA), or verb intensifiers. This linguistic feature often poses challenges when translating Sundanese into foreign languages, particularly European languages. However, we argue that Sundanese KA demonstrates a higher degree of translatability into Japanese, a language that also uses verb intensifiers similar to those found in Sundanese. In Japanese, words analogous to Sundanese KA are categorized as giongo-gitaigo, although the term onomatope is more commonly used. This study aims to identify Sundanese KA based on Tamori’s classification of Japanese onomatopoeia. Using a descriptive-qualitative approach, we examine (Sound [S] and Mentality [M]) onomatopoeia. The findings reveal that Sundanese onomatopoeic and non-onomatopoeic KA align with their respective Japanese counterparts as classified by Tamori, based on their associations with sensations, perceptions, emotional states, and the descriptions of activities.